2008
DOI: 10.1093/nar/gkn360
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Methanocaldococcus jannaschii RNase P reveal insights into the roles of RNA and protein cofactors in RNase P catalysis

Abstract: Ribonuclease P (RNase P), a ribonucleoprotein (RNP) complex required for tRNA maturation, comprises one essential RNA (RPR) and protein subunits (RPPs) numbering one in bacteria, and at least four in archaea and nine in eukarya. While the bacterial RPR is catalytically active in vitro, only select euryarchaeal and eukaryal RPRs are weakly active despite secondary structure similarity and conservation of nucleotide identity in their putative catalytic core. Such a decreased archaeal/eukaryal RPR function might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
113
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(125 citation statements)
references
References 43 publications
12
113
0
Order By: Relevance
“…The formation of a complex between Pop5 and Rpp1 is consistent with the available results of two-hybrid studies and pull-down experiments performed for yeast RNases MRP/P (HouserScott et al 2002;Aspinall et al 2007) as well as with the results obtained for archaeal homologs of Pop5 and Rpp1 (Tsai et al 2006;Pulukkunat and Gopalan 2008;Honda et al 2010).…”
Section: Introductionsupporting
confidence: 89%
“…The formation of a complex between Pop5 and Rpp1 is consistent with the available results of two-hybrid studies and pull-down experiments performed for yeast RNases MRP/P (HouserScott et al 2002;Aspinall et al 2007) as well as with the results obtained for archaeal homologs of Pop5 and Rpp1 (Tsai et al 2006;Pulukkunat and Gopalan 2008;Honda et al 2010).…”
Section: Introductionsupporting
confidence: 89%
“…3A; see SI Text). Our previous in vitro reconstitution studies of Mja and Pfu RNase P revealed that the functional units are not individual proteins but are binary RPP complexes (POP5•RPP30 and RPP21•RPP29) (25,26). This observation led us to purify these RPP pairs as complexes after their cooverexpression in Eco; moreover, RNase P assembled from Pfu RPR and RPPs, purified either individually or as binary complexes, exhibits comparable k cat and K m values (29).…”
Section: Resultsmentioning
confidence: 99%
“…1) (24). Type M RPRs possess a smaller, atypical L15 and lack P16, P6, and P8; these changes might adversely impact substrate binding, an expectation based on findings from the related bacterial RPR (24,25). Interestingly, the inclusion of L7Ae lowers the K m to 0.044 μM for pre-tRNA Tyr processing by Mma RNase P. Clearly, RPPs (including L7Ae) somehow remedy the substrate-binding defects of the Mma RPR.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations